On Micro-generalized Closed Sets and Micro-generalized Continuity in Micro Topological Spaces (European Journal of Pure and Applied Mathematics, 2021)
The  purpose of this paper is to  define and study  a new  class of sets called micro  generalized  closed sets and define  micro generalized continuous function and irresolute micro generalized continuous function  in micro topological spaces. Basic properties of micro generalized closed sets  and its characterizations are analyzed.
Keywords: generalized closed; nano topology; nano generalized closed; micro topology; micro generalized closed; micro generalized continuous function; irresolute micro generalized continuous function